2018
DOI: 10.1007/s12046-018-0814-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsation on the near flow field of a submerged water jet

Abstract: The current study investigates the effect of pulsation frequency on the near field characteristics of a submerged water jet using the technique of dye visualization. Flow visualization was performed in water over the range: Reynolds number 540-1540, Strouhal number 0.16-1.75, and at constant amplitude of pulsation of 18%. The results show that the mixing and entrainment process at lower Reynolds number occurs due to diffusion process owing to relatively stable shear layer for the case of a steady jet, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The utilization of segmentation and edge or object detection techniques is crucial to derive important flow physical quantities from output data obtained through imaging methods. Examples of features that may be sought include, the coordinates of a dye plume (Yadav 2018), oil or smoke patterns (Arivoli 2023), the position of a shock wave (Kováics et al 2023), vortical structures (Lindner et al 2020) or particle clusters (Metzger et al 2022), species concentrations and iso-surfaces (Zheng et al 2022), interfaces and zones (Reuther and Kähler 2018). The methodologies applied in this context span a range of experimental techniques (Tropea et al 2007), including chemiluminescence (CL) (Guethe et al 2012), laser induced fluorescence (LIF) (Eghtesad et al 2024) and phosphorescence (LIP) (Charogiannis 2013), filtered Rayleigh scattering (FRS) (Doll et al 2023), thermography (Astarita et al 2006), schlieren imaging and shadowgraphy (Settles and Hargather 2017), high-speed photography (Versluis 2013), dye injection (Di et al 2022), smoke visualization (Willmott et al 1997), oil film measurements (Cai et al 2022) as well as experiments involving shear-or temperature/pressuresensitive liquid crystals (SLC, TLC) (Ireland and Jones Jul 2000) and paints (TSP, PSP) (Gregory et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of segmentation and edge or object detection techniques is crucial to derive important flow physical quantities from output data obtained through imaging methods. Examples of features that may be sought include, the coordinates of a dye plume (Yadav 2018), oil or smoke patterns (Arivoli 2023), the position of a shock wave (Kováics et al 2023), vortical structures (Lindner et al 2020) or particle clusters (Metzger et al 2022), species concentrations and iso-surfaces (Zheng et al 2022), interfaces and zones (Reuther and Kähler 2018). The methodologies applied in this context span a range of experimental techniques (Tropea et al 2007), including chemiluminescence (CL) (Guethe et al 2012), laser induced fluorescence (LIF) (Eghtesad et al 2024) and phosphorescence (LIP) (Charogiannis 2013), filtered Rayleigh scattering (FRS) (Doll et al 2023), thermography (Astarita et al 2006), schlieren imaging and shadowgraphy (Settles and Hargather 2017), high-speed photography (Versluis 2013), dye injection (Di et al 2022), smoke visualization (Willmott et al 1997), oil film measurements (Cai et al 2022) as well as experiments involving shear-or temperature/pressuresensitive liquid crystals (SLC, TLC) (Ireland and Jones Jul 2000) and paints (TSP, PSP) (Gregory et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Yadav and Agrawal [15] investigated the effect of pulsation frequency on the near-field characteristics of a submerged water jet using the technique of dye visualization. e results showed that the initiation and growth of vortices in the shear layer depends on the pulse frequency.…”
Section: Introductionmentioning
confidence: 99%